PERAN PEMEDIASI KEPUASAN PADA HUBUNGAN ANTARA WEBPORTAL TERHADAP DAMPAK INDIVIDU - Wiry Utami; Purbo Jadmiko; Elfitra Azliyanti (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2020)
The study aims to analyze the effect of webportal on individual impact and satisfaction as mediating variable. Sample in this study are 381 respondents. This study is using survey. The technique of taking sample is by using convenience sampling. The hypothesis testing was conducting using multiple regression analysis and hierarchical regression analysis. The result showed that webportal has positive and significant on individual impact. Webportal also has positive and significant on satisfaction. Satisfaction partial mediation the positive influence of webportal on individual impact.